The status of the video collections of the University of the Philippines Diliman libraries and the information behavior for video materials among the faculty members - Arinuelo, Lileth L.; Apolinario, Rhea Rowena U.; Ramos-Eclevia, Marian S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
This study investigates the present state of the UP Diliman libraries' video collections and how the faculty members utilize different sources, including the library, to fulfill their work-related needs for video materials. Differences in attitude between faculty users and non-users of video materials, and between faculty and librarians were also investigated.
Using descriptive and correlational research, two separate instruments were administered to 35 head librarians and 150 faculty members of UP Diliman.
The study found that use and non-use vary significantly across the four college clusters (Arts and Letters, Social Sciences and Law; Management and Economics; and Science and Technology) of UP Diliman. Moreover, the study found a discrepancy between the use pattern of the faculty and the available materials in the UP libraries' video collections. The faculty members are mostly using digital formats and are very comfortable with new technology. On the other hand, most of the UP libraries' video collections are is in analog format and non-networkable.
Confirming Wilson's (1999) model of information behavior, the study found that level of satisfaction and level of success in use are correlated to the frequency of use for sources of video materials. In terms of difference in attitudes, the study found that faculty users of video materials have more positive attitudes than non-users on (a) use of videos in class, (b) use of videos in the future, and (c) library support for collection development. Meanwhile, librarians have more positive attitudes than the faculty regarding the use of videos in class; faculty members have more positive attitudes than librarians on library support.
Recommendations include long-term plans related to moving the video collections into the digital environment.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Video recordings -- Philippines -- Quezon City -- Use studies; Libraries -- Special collections -- Video recordings